A decade of changes in clinical characteristics and management of elderly patients with non-ST elevation myocardial infarction admitted in Italian cardiac care units. Issue 1 (15th December 2014) - De Luca, Leonardo; Olivari, Zoran; Bolognese, Leonardo; Lucci, Donata; Gonzini, Lucio; Di Chiara, Antonio; Casella, Gianni; Chiarella, Francesco; Boccanelli, Alessandro; Di Pasquale, Giuseppe; Bovenzi, Francesco M; Savonitto, Stefano
Abstract : Objective: To describe the evolution of clinical characteristics, in-hospital management and early outcome of elderly patients with non-ST elevation myocardial infarction (NSTEMI). Methods: We analysed data from five consecutive Italian nationwide registries, conducted between 2001 and 2010, including patients with acute coronary syndromes admitted to cardiac care units (CCUs). Results: Of 10 983 patients with NSTEMI enrolled in the 5 surveys, 4350 (39.6%) were ≥75 years old (mean age 81±5 years). Some clinical characteristics such as diabetes mellitus, hypertension, renal dysfunction and previous percutaneous coronary intervention increased significantly, whereas a history of stroke, myocardial infarction and heart failure decreased over time. An invasive approach increased from 26.6% in 2001 to 68.4% in 2010 (p<0.0001) and revascularisation rates increased from 9.9% to 51.7% (p<0.0001). Early use and prescription at discharge of β-blockers, statins and dual antiplatelet treatment increased significantly (p<0.0001). Thirty-day observed mortality decreased from 14.6% (95% CI 9.9 to 20.4) to 9.5% (95% CI 7.7 to 11.6). At the multivariate logistic regression analyses adjusted for baseline characteristics, compared with 2001, the risk of death was significantly lower in all the other studies performed at different times with reductions in adjusted mortality between 66% and 45%. Conclusions: Over the past decade, substantial changes have occurred in the clinical characteristics and management of elderly patients admitted with NSTEMI in Italian CCUs, with a greater use of revascularisation therapy and recommended medications. These variations have been associated with a reduction in 30-day adjusted mortality rate.